Identification of Economic Structure Transformation of Banyuwangi Regency: A Study of Economic Sectors Using Location Quotient, Shift Share, and Klassen Typology Methods - Himmah, Faiqotul; Priana, Wiwin (Yayasan Riset dan Pengembangan Intelektual, 2025)
This research aims to identify the transformation of the economic structure in Banyuwangi Regency during the period 2019-2023 by analysing the contribution of various economic sectors using Location Quotient (LQ), Shift Share, and Klassen Typology methods. The study adopts a descriptive quantitative approach, utilising secondary data obtained from the Central Bureau of Statistics (BPS), including the Gross Regional Domestic Product (GRDP) at constant prices. The LQ analysis reveals a gradual decline in the number of basic sectors, from five in 2019 to four in 2023, with the transport and warehousing sector losing its basic status due to reduced comparative advantage. The Shift Share analysis indicates a significant increase in the number of sectors with positive differential shift values, reflecting an expansion in regional competitiveness and the spread of economic growth to previously lagging sectors. Furthermore, the Klassen Typology analysis shows a shift in Banyuwangi's classification from Quadrant IV (relatively underdeveloped region) to Quadrant III (advanced but depressed region), suggesting a meaningful phase of catch-up growth. These findings demonstrate an ongoing structural transformation from primary to more diverse secondary and tertiary sectors, aligning with regional development theories that emphasise productivity enhancement and sectoral diversification. The study concludes that while Banyuwangi is on a promising trajectory towards a more balanced and resilient regional economy, sustained strategic efforts are needed to improve per capita income and further strengthen inter-sectoral linkages for long-term equitable development.